Demystifying Theoretical Sampling in Grounded theory Research - Jenna Breckenridge; Derek Jones (Grounded Theory Review: An International Journal, 2009)
Theoretical sampling is a central tenet of classic grounded theory and is essential to the development and refinement of a theory that is ‘grounded’ in data. While many authors appear to share concurrent definitions of theoretical sampling, the ways in which the process is actually executed remain largely elusive and inconsistent. As such, employing and describing the theoretical sampling process can present a particular challenge to novice researchers embarking upon their first grounded theory study. This article has been written in response to the challenges faced by the first author whilst writing a grounded theory proposal. It is intended to clarify theoretical sampling for new grounded theory researchers, offering some insight into the practicalities of selecting and employing a theoretical sampling strategy. It demonstrates that the credibility of a theory cannot be dissociated from the process by which it has been generated and seeks to encourage and challenge researchers to approach theoretical sampling in a way that is apposite to the core principles of the classic grounded theory methodology.